An Analysis Of Students’ Difficulties In Reading Comprehension At Class IX Of SMPN 5 Jombang - Alifah, Nur Alifah; Maskhurin Fajarina (Fakultas Ilmu Pendidikan Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
While reading comprehension is an essential skill for interpreting written texts, understanding English reading materials remains a significant challenge for many junior high school students. This study aims to systematically identify the reading comprehension difficulties experienced by ninth-grade students at SMPN 5 Jombang and analyze their underlying causes. Using a descriptive qualitative approach, the research involved 32 students from Class IX C and one English teacher. Data were collected through classroom observations, semi-structured interviews, and open-ended questionnaires, then analyzed using data reduction, data display, and conclusion drawing. The findings reveal four major difficulties: identifying main ideas, locating specific information, understanding English vocabulary, and comprehending long sentence structures. Among these, limited vocabulary mastery emerged as the primary barrier to reading comprehension. The study also found that limited vocabulary knowledge, ineffective reading strategies, and insufficient background knowledge were the main factors contributing to these difficulties. Therefore, strengthening vocabulary mastery and teaching effective reading strategies are essential to improve students' reading comprehension. These findings are expected to help EFL teachers enhance instructional practices and provide a reference for future research..